(untitled) (Research, Society and Development, 2022)
The objectives of the present study were: to contextualize undergraduate students about the bioinformatics theme; propose strategies for conducting Scientific Initiation projects in times of a pandemic caused by the new coronavirus, making it possible to carry out research in the remote format. This research is an observational, cross-sectional and descriptive study carried out in the years 2020 and 2021, with the participation of undergraduate and technical course students in the areas of Agricultural Sciences and Information Systems, with 2 PIBIC undergraduate scholarship holders, 2 PIBIC-EM scholarship holders from the technical course for the project and volunteer students. In the present work, the following methodological strategies were adopted: application and selection of scholarship students; definition of themes; theoretical-practical thematic workshops; systematic literature review and; bioinformatics analysis, using the STITCH and CYTOSCAPE platforms. Preparation of scientific work for publication and/or presentation at an event. Faced with the current pandemic scenario, face-to-face activities have been interrupted. Thus, meetings were held in a virtual way, in which there was a previous reading of reports and materials about the themes and, a discussion based on the material collected. The critical sense of academics was constantly explored. In the bioinformatics analyses, the students were able to elaborate and interpret several chemical-protein interaction networks using as inputs in the STITCH platform some chemical compounds from the plants Cagaiteira, Alecrim-pimenta and Neem and different species. It is concluded that research projects that are conducted through bioinformatics analysis are extremely important for Scientific Initiation students in times of social isolation in the midst of the COVID-19 pandemic.